Fish oil replacement with vegetable oils using different sources of fish meal in pelleted feeds for juvenile Tiger grouper, Epinephelus fuscoguttatus - Norfazreena Mohd Faudzi (2013)
Tiger grouper, Epinephelus fuscoguttatus, is a high value marine fish, which belongs to Serranidae family. Rapid development of marine fish farming industry has increased the demand of this species. In order to reduce the dependence on wild fish stock and to develop cost–effective feed for grouper culture, three experiments were carried out to replace fish oil with vegetable oils using different sources of fish meal in the feeds of juvenile tiger grouper. Experiment 1 was conducted to screen the performance of different types of vegetable oils in the feeds for juvenile tiger grouper. Four experimental feeds (50% crude protein and 13% crude lipid; 57% replacement level of lipid) with different type of oil sources (Fish oil, FO; Canola oil, CNO; Refined, bleached, deodorized palm olein, RBDPO; Soybean oil, SBO) were formulated using local fish meal as a protein source. Triplicate group of twenty individual juvenile tiger grouper with mean body weight 42.8±0.6 g were stocked in 100 L fiberglass tanks and fed the experimental feeds at apparent satiation level twice a day for 6 weeks duration. The results showed that vegetable oils were able to replace fish oil without adverse effect on survival, growth and feed conversion ratio (FCR) of fish. Experiment 2 was conducted to further investigate the performance of vegetable oils in juvenile tiger grouper using laboratory-made fish meal as a protein source. Apart from growth performance and feed utilization, body proximate composition, hematological parameter and costbenefit analysis were also determined in this experiment. Similar to the Experiment 1, 5 experimental feeds were formulated with 50% crude protein and 10% crude lipid at 50% replacement level. CNO, RBDPO and SBO treatments and a mixture of CNO, RBDPO and SBO with ratio 1:1:1 were tested. In general, the result showed an improvement on fish performance after changing the protein source. Survival rates in this experiment were above 86% in all dietary treatments. Weight gain (WG) was highest in CNO treatment followed by MIX, SBO, RBDPO and FO. No significant difference (P>0.05) was observed in FCR among the dietary treatments. Except for viscerosomatic index, body indices were independent of feeds. Protein and lipid contents of fish carcass were lowest in the FO treatment. Except for triglycerides content, no significant difference (P>0.05) was observed in the hematological parameter of FO and vegetable oil-based treatments. Feed cost calculation shows replacement of fish oil with vegetable oil is able to reduce the feed cost to culture juvenile tiger grouper. Experiment 3 was conducted to compare the performance of fish when fish oil was replaced with vegetable oils in the feeds based on high quality fish meal in combination of 15% defatted soybean meal. Even though the protein source was changed, vegetable oil–based feeds did not affect the performance of juvenile tiger grouper. In conclusion, at least 50% of fish oil can be replaced with vegetable oils in the feeds for juvenile tiger grouper regardless the source of fish meal. These findings are considered important towards reducing dependency of grouper culture industry on fish-based ingredients.